Enhanced ferromagnetism and glassy state in phase separated La0.95Sr0.05MnO3 + δ - De, K. (2012)
Unusual high temperature ferromagentism is reported for La0.95Sr0.05MnO3+δ with Curie temperatures (TC1 and TC2) TC1 at 290 K and TC2 ∼ 150 K. Weak antiferromagnetism (AFM) is thought to give low moment, low temperature irreversibility, and non-saturation up to 10 T at 5 K. A short-range ferromagnetism is predicted from well-defined hysteresis at 5 K and field-cooled (FC) magnetization curves. Strong irreversibility between zero field-cooled (ZFC) and FC at 5 T is due to “hard” spins, not from ferromagnetic clusters. Field-dependent peak shift of spin freezing temperature in ZFC, memory effect, magnetic relaxation shows cluster glass like transition in the system. A metal-insulator transition at 115 K also implies a completion of percolation of short range ferromagnetic clusters, giving an onset of metallic state at 115 K. A complete magnetic phase diagram is presented showing its temperature dependent rich magnetic behavior.